THE DISTRIBUTION AND SOIL CARBON STOCK ON LAND UTILITY TYPES OF BUSH, MOOR, MIXED GARDEN AND RAINFED RICE FIELDS ON DRY LAND IN ACEH BESAR REGENCY - Abdullah, Umar Husein; Endiyani, Endiyani; Irhami, Irhami; Agustina, Sri; Akbar, Yusran (ITScience (Information Technology and Science), 2023)
This study aims to determine the potential of soil carbon on dry land in Aceh Besar regency. This study uses a descriptive method based on field results and surveys and laboratory analysis. Soil sampling at various depths was carried out for carbon and bulk density analysis. Composite soil samples were taken at a depth of 0-5, >5-10, >10-20, >20-30, >30-70, and >70-100 cm. The type of land use is bush covering an area of ??96,962.2 ha, moor 313.03 ha, rainfed rice fields 4,478.67 ha and mixed gardens 15,052.09 ha. The highest percentage of soil carbon is in the mixed garden land utility type (3.40%) compared to other types of utility. the highest carbon potential is found in the bush land utility type (137.68 tons/ha) compared to other types of utility. The highest soil carbon stock is in the type of land use of bush compared to other types of land utility. This is because the bush land utility type has soil carbon potential and a large area compared to other land utility types.